Valoración de los canales de comercialización del rubro Naranja (Citrus sinensis L.) en el cantón Caluma, provincia Bolívar - Ledesma Jiménez, María Fernanda (2017)
The orange is considered as the main item of commercialization, represents the most important activity in Caluma, as much in surface as in value of the production. In recent years it is facing problems in profitability, due to factors such as production, consumption and forms of commercialization. The objectives were to: Identify the actors involved in the marketing process, determine the destination markets for the fruit, establish marketing channels. The methodology used was through a survey and application of surveys conducted in modules; Its analysis through descriptive statistics and the classification of data in a Microsoft Office Excel base according to the requirements. The main results obtained are that 52.6% cultivate valence variety; The months of greatest production are July, August and September; 79% produce the harvest themselves, 96% sell the production to intermediaries, 63% say that production is profitable; Of the intermediaries 90% are men and market more with common variety and valencia, 90% buy the producers in the plantation. The months of lowest price are April, May and June; And higher prices October, November and December. 90% use a truck as a means of transportation, 50% sell in wholesale markets and popular fairs in Quito, Guayaquil and Machala. Among the conclusions we indicate that the actors that play an active role in the marketing chain are: agricultural producer, intermediary and final consumer. We also show that the producer and the intermediary are in charge of establishing the system of marketing and supplying the fruit to the most affluent markets, Quito, Guayaquil, Machala and Cuenca; Mainly to these cities due to high population growth and consumption habits. I recommend strengthening the organization between producers and intermediaries, establishing maintenance prices to avoid losses, that production goes through processes of processing and transformation that generate added value and therefore improves the income of producers.